Adult mortality in sub-saharan Africa, Zambia: Where do adults die? - Vesper H. Chisumpa; Clifford O. Odimegwu; Nicole De Wet (Elsevier, 2017)
Place of death remains an issue of growing interest and debate among scholars as an indicator of quality of end-of-life care in developed countries. In sub-Saharan Africa, however, variations in place of death may suggest inequalities in access to and the utilization of health care services that should be addressed by public health interventions. Limited research exists on factors associated with place of death in sub-Saharan Africa. The study examines factors associated with the place of death among Zambian adults aged 15-59 years using the 2010-2012 sample vital registration with verbal autopsy survey (SAVVY) data, descriptive statistics and multivariate logistic regression analysis. Results show that more than half of the adult deaths occurred in a health facility and two-fifths died at home. Higher educational attainment, urban versus rural residence, and being of female gender were significant predictors of the place of death. Improvement in educational attainment and investment in rural health facilities and the health care system as a whole may improve access and utilization of health services among adults.